Water-controlled selectivity switch in a multicomponent reaction: One-pot stereoselective synthesis of (acyloxymethylidene)chromonyl-furochromones and amido-(acyloxymethylidene)chromones. (10th September 2021) - Teimouri, Mohammad Bagher; Batebi, Elham; Mohammadnia, Shabnam; Khavasi, Hamid Reza
Abstract: An efficient protocol for the selective synthesis of (acyloxymethylidene)chromonyl-furochromones or amido-(acyloxymethylidene)chromones via a water-controlled multicomponent cascade reaction of 3-formylchromones, linear carboxylic acid anhydrides, and alkyl isocanides in CH2 Cl2 has been developed. (Acyloxymethylidene)chromonyl-furochromones were obtained in dry CH2 Cl2 ; conversely, amido-(acyloxymethylidene)chromones were formed with wet CH2 Cl2 (undried dichloromethane) as the solvent at room temperature. The reaction proceeds via the formation of a highly reactive O -acylatedoxonium intermediate, generated from the reaction between 3-formylchromones and linear carboxylic acid anhydrides. The subsequent trapping of the O -acylatedoxonium ion by aminofurochromone intermediate in situ generated by cycloaddition reaction of alkyl isocyanide and the second equivalent of 3-formylchromone in dry CH2 Cl2, would give (acyloxymethylidene)chromonyl-furochromones in excellent diastereoselectivity and yields. Alternatively, O -acylatedoxonium intermediate could be also regioselectively trapped by α-addition of alkyl isocyanides in wet CH2 Cl2 to provide amido-(acyloxymethylidene)chromones in good yields. Graphical abstract: Image 1